2014
DOI: 10.1177/0269215514564897
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility and pilot randomized controlled trial of the “Timing it Right Stroke Family Support Program”

Abstract: Preliminary findings suggest the research design is feasible, caregivers' needs are complex, and the support intervention may enhance caregivers' perceived support and mastery. The intervention will be tested further in a large scale trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 47 publications
1
62
0
Order By: Relevance
“…For example, three of the caregiver studies did not measure survivor outcomes, 9,10,13 and the two that did, 11,12 did not find significant results. All of the dyad intervention studies reported at least one significant caregiver outcome; however, most were primarily targeted toward the survivor with positive survivor outcomes.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…For example, three of the caregiver studies did not measure survivor outcomes, 9,10,13 and the two that did, 11,12 did not find significant results. All of the dyad intervention studies reported at least one significant caregiver outcome; however, most were primarily targeted toward the survivor with positive survivor outcomes.…”
Section: Resultsmentioning
confidence: 97%
“…9,10,13,14,17,18 One large study used cluster randomization by unit. 11 The remaining three studies were quasi-experimental (e.g., non-random assignment to condition 12,16 or single group 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations